Colorectal cancer susceptibility loci on chromosome 8q23.3 and 11q23.1 as modifiers for disease expression in lynch syndrome. Issue 4 (19th November 2010) - Talseth-Palmer, Bente A; Brenne, Ingvild S; Ashton, Katie A; Evans, Tiffany-Jane; McPhillips, Mary; Groombridge, Claire; Suchy, Janina; Kurzawski, Grzegorz; Spigelman, Allan; Lubinski, Jan; Scott, Rodney J
Abstract : Objective: Recently, six colorectal cancer (CRC) susceptibility loci have been identified, and two single-nucleotide polymorphisms (SNPs)—rs16892766 (8q23.3) and rs3802842 (11q23.1)—from two of these regions have been found to be significantly associated with an increased CRC risk in patients with Lynch syndrome. The objective of this study was to genotype nine SNPs within these six loci to confirm previous findings and investigate whether they act as modifiers of disease risk in patients with Lynch syndrome. Design: The patient cohort consisted of 684 mutation-positive patients with Lynch syndrome from 298 Australian and Polish families. Nine SNPs were genotyped: rs16892766 (8q23.3), rs7014346 and rs6983267 (8q24.21), rs10795668 (10p14), rs3802842 (11q23.1), rs10318 and rs4779584 (15q13.3), and rs4939827 and rs4464148 (18q21.1). The data were analysed to investigate possible associations between the presence of variant alleles and the risk of developing disease. Results: An association between SNP rs3802842 on chromosome 11q23.1 and rs16892766 on chromosome 8q23.3 and the risk of developing CRC and age of diagnosis was found in MLH1 mutation carriers. Female MLH1 mutation carriers harbouring the homozygous variant genotype for SNP rs3802842 have the highest risk of developing CRC. When the number of risk alleles for the two SNPs combined was analysed, a difference of 24 years was detected between individuals carrying three risk alleles and those carrying no risk alleles. Conclusion: The authors were able to replicate the association between the CRC susceptibility loci on chromosomes 8q23.3 and 11q23 and the risk of developing CRC in patients with Lynch syndrome, but the association could only be detected in MLH1 mutation carriers in this study.